Oral 17β-estradiol/progesterone (TX-001HR) and quality of life in postmenopausal women with vasomotor symptoms. Issue 5 (May 2019) - Simon, James A.; Kaunitz, Andrew M.; Kroll, Robin; Graham, Shelli; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: The aim of the study was to describe the effects of TX-001HR (17β-estradiol [E2] and natural progesterone [P4] in a single oral capsule) on menopause-specific quality of life in women with moderate to severe vasomotor symptoms (VMS). Methods: The REPLENISH study (NCT01942668) was a phase 3, randomized, double-blind, placebo-controlled, multicenter trial which evaluated four E2/P4 doses in postmenopausal women with VMS and a uterus. Women with moderate to severe hot flushes (≥7/d or ≥50/wk) were included in a VMS substudy. Participants self-administered the Menopause-Specific Quality of Life (MENQOL) questionnaire. Baseline changes in MENQOL overall and domains were determined as well as correlations between changes in MENQOL scores and VMS frequency or severity. Results: In the VMS substudy, women treated with E2/P4 had significantly greater improvements from baseline in their MENQOL overall score at week 12, and months 6 and 12, compared with placebo (all, P < 0.05, except the lowest E2/P4 dose at months 6 and 12). Improvements from baseline for the MENQOL vasomotor domain score were significantly greater with TX-001HR doses versus placebo at all time points (all, P < 0.01). Changes in MENQOL vasomotor scores moderately correlated with changes in VMS frequency ( r = 0.56, P < 0.0001) and severity ( r = 0.55, P < 0.0001). Conclusion: In the REPLENISH trial, women with moderate to severe VMS treated with most E2/P4 doses reported significant improvements in quality of life from baseline to 12 weeks compared with placebo, which were maintained up to 12 months. TX-001HR, if approved, may provide the first oral hormone therapy formulation in a single capsule containing E2 and P4 for the treatment of VMS in postmenopausal women with a uterus.